The problem of literature currents in literary criticism (Eurasian Journal of Philology Science and Education, 2016)
The article examines the place and role of the naturalistic course in the Kazakh literature. The author studies the study of the flow in the literary science as currents, common in many countries. Comprehensively analyzes the naturalistic trend in the national literary criticism, which originated in the late XIX century in Western Europe and through Russian literature penetrated into Kazakh. It shows its influence on the Kazakh literature and describes it in works of art. It cites opinions of naturalism in the Kazakh literary criticism, and such scientists as E. Ismailov, M. Karataev, T. Kakishev, R.Nurgali and as a researcher-scholar of independence Zh. Zharylgapov. The article also investigates issues such naturalism as the study of man from the biological point of view, the excessive attention to domestic detail, allegorical description of such products, strict adherence to the laws of language, gain publicist content of the work. Author on the analysis of Kazakh art works proves the existence of the elements of naturalism in the national literature
Keywords: naturalism; flow; kazakh literature; literary criticism; piece of art; literary scholar; detail.